2017
DOI: 10.5547/01956574.38.si1.ldav
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental Cost of Global Fuel Subsidies

Abstract: Despite increasing calls for reform many countries continue to provide subsidies for gasoline and diesel. This paper quantifies the external costs from global fuel subsidies using the latest available data and estimates from the World Bank and International Monetary Fund. Under preferred assumptions about supply and demand elasticities, current subsidies cause $44 billion in external costs annually. This includes $8 billion from carbon dioxide emissions, $7 billion from local pollutants, $12 billion from traff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 31 publications
(51 reference statements)
2
22
0
Order By: Relevance
“…Progressively raising public capital expenditures may well function as a desirable mechanism, however, if the future oil income in the KSA happens to diminish over time, whether because of lower prices on world markets and/or lower domestic production mirroring lower world demand. While our results are in line with the partial equilibrium analysis of welfare effects of price reforms (Davis, 2017), our paper confirms that the result holds in general equilibrium. More importantly, our paper provides additional insights into intergenerational redistributive effects of higher retail energy prices that are especially useful for oil-exporting countries with young and fast-growing populations.…”
Section: Resultssupporting
confidence: 89%
“…Progressively raising public capital expenditures may well function as a desirable mechanism, however, if the future oil income in the KSA happens to diminish over time, whether because of lower prices on world markets and/or lower domestic production mirroring lower world demand. While our results are in line with the partial equilibrium analysis of welfare effects of price reforms (Davis, 2017), our paper confirms that the result holds in general equilibrium. More importantly, our paper provides additional insights into intergenerational redistributive effects of higher retail energy prices that are especially useful for oil-exporting countries with young and fast-growing populations.…”
Section: Resultssupporting
confidence: 89%
“…Therefore, the income effect of the rebate limited the expected decrease in energy prices. As an example from another country, it was predicted that gasoline consumption would decrease by 53% in Saudi Arabia if its price were hiked to the global spot market price, an approximately 256% increase (Davis, 2017).…”
Section: Predicted Changes In Energy Consumptionmentioning
confidence: 99%
“…Artificially low fuel prices also resulted from Turkmenistan's protracted subsidisation practice: Lucas Davis (2016) reported that, in 2014, a litre of gasoline bought in Turkmenistan would cost no more than US$ 0.20. Beyond energy, Turkmenistan's subsidisation system also included "water, salt, flour and other goods" (ICG 2003).…”
Section: Tapi: a Virtual Remedy For Turkmenistan's Export Crisismentioning
confidence: 99%